Optimised extraction and prementation processes curcuma caesia extractive on antioxcidant activity for potential application in cosmeceutitcals - Siti Fathimah Putery Jemain (Kulliyyah of Engineering, International Islamic University Malaysia, 2021)
The global skincare industry offers a wide range of products, however, these products are possible sources of human exposure, to endocrine-disrupting chemicals. Thus, this thesis is a pioneering research on the locally grown Curcuma caesia that has been used as a traditional folk medicine but has not been extensively studied, by optimizing its extraction parameters, fermentation parameters and the preparation of anti-acne soap and anti-acne cream from its fermented extract. Deionized water is the solvent of choice based on its halal, safe and abundance nature. The 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavengers were extracted using the ultrasonic water bath and its suitable extraction frequency was selected based on a one factor at a time (OFAT) study. It can be stated that pH and temperature significantly influenced the extraction yield of phenolics from C. caesia and improved the DPPH scavenging activity of the extracted bioactive compounds. The optimization study with varying extraction temperature, pH and time using face centered central composite design (FCCCD) under response surface methodology (RSM) showed that pH 6, a temperature of 60℃ and an extraction time of 30 minutes was the most efficient extraction parameters that exhibited high yield of phenolics and high DPPH scavenging activity. A total number of 20 experimental runs with 6 centre points were carried out. The obtained results were analyzed using design expert and statistical validation indices to check the adequacy of the obtained quadratic models. The analysis of variance (ANOVA) showed that more than 97% of the variation was explained by the models, hence, there was a good agreement between experimental and predicted data at optimum conditions. All the independent variables had a significant effect (p<0.05) on all responses which indicated that all extraction parameters employed in this study were important in the optimization process. The R2 value for DPPH scavenging activity was 0.9782, suggesting that the quadratic polynomial models developed were satisfactorily accurate to be used in analyzing the interactions of the parameters (response and independent variables). The Plackett Burman experimental design was employed in searching for significant media components that influence DPPH scavenging activity amongst the 11 chosen variables and they were optimized using FCCCD by Design Expert software version 6.0.8. Yeast extract, peptone and sucrose were found to be the critical factors influencing DPPH scavenging activity. Optimum DPPH scavenging activity with these factors was deduced using FCCCD. The highest DPPH scavenging activity of 84.25 % was obtained when concentration of yeast extract, peptone and sucrose was at 7, 8 and 10 (g/L), respectively with C. caesia concentration of 2 % (v/v) and L. plantarum concentration of 2 % (v/v). The supernatant of the optimized media was used to measure the 5–lipoxygenase (5-LOX) inhibition activity as an indicator of anti-inflammatory activity present in the supernatant and the mean activity recorded was 76.84%. Twenty respondents with acne vulgaris were selected to test the efficacy and safety of the anti-acne facial soap and cream formulated from the fermented C. caesia supernatant. A split face trial was carried out daily for seven days period. Significant lesion improvements and reduced numbers of acne lesions were observed on the treated side of the face. No erythema, burning, stinging, scaling, drying or edema of the skin or exacerbation of the pre-existing acne were recorded. A student’s paired t-test was carried out to test the reliability of the results and the obtained p value of less than 0.05 indicates that the result is significant and that it can be replicated in a larger population.